1990
DOI: 10.1093/nar/18.3.687
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative Hpall-PCR assay to measure methylation of DNA from a small number of cells

Abstract: Methylation-sensitive restriction enzymes and Southern blot analysis are commonly used to assay for DNA methylation, usually requiring DNA from about 105 cells. However sensitivity adequate for only a few hundred cells is needed in many cases, for example, the study of DNA methylation changes in germ cells or pre-implantation embryos. We earlier reported a sensitive PCR assay using primers that bracket a Hpall site; if the DNA is treated with HpaII prior to PCR, an amplified product is seen only from a methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
1
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(90 citation statements)
references
References 3 publications
1
87
1
1
Order By: Relevance
“…In these samples, only two bladder cancer cases showed p16 promoter hypermethylation. This result is lower than our previous observations (14% vs 67%) of p16 exon 1 methylation in bladder TCCs (Gonzalez-Zulueta et al, 1995a) which was measured by the PCR based methylation analysis (Singer-Sam et al, 1990). We have, however, recently shown that methylation of the coding region in exon 1 does not inhibit the initiation of p16 transcription (Gonzalgo et al, 1998).…”
Section: Discussioncontrasting
confidence: 71%
“…In these samples, only two bladder cancer cases showed p16 promoter hypermethylation. This result is lower than our previous observations (14% vs 67%) of p16 exon 1 methylation in bladder TCCs (Gonzalez-Zulueta et al, 1995a) which was measured by the PCR based methylation analysis (Singer-Sam et al, 1990). We have, however, recently shown that methylation of the coding region in exon 1 does not inhibit the initiation of p16 transcription (Gonzalgo et al, 1998).…”
Section: Discussioncontrasting
confidence: 71%
“…27 We digested genomic DNAs either with MspI, which cleaves the CpG regardless of the methylation status, or with HpaII, which cleaves only unmethylated CpG. We then performed PCR with 3 pairs of primers designed for the promoter regions of the Dkk3 gene.…”
Section: Methylation At the Promoter Region Of Dkk3 With Transcriptiomentioning
confidence: 99%
“…Restriction digestion with methylation sensitive enzymes using Southern blot 39 is an alternative method, and can be allele-specific if the region contains a suitable RFLP, but requires large amounts (about 10 μg) of genomic DNA. PCR detection of the methylation-sensitive site 40 requires less DNA but is not allele-specific. The drawback of these bisulfite-and restriction enzyme based methods is that they do not distinguish between 5mC and 5hmC.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%